Analysis of the Influence of Open Unemployment Rate, Road Infrastructure Development, Inflation, and Economic Growth on Poverty Levels in Mataram City (2010-2023) - Ilmi, Amalia; Jufri, Akhmad (PT FORMOSA CENDEKIA GLOBAL, 2024)
Although economic growth had started to improve at the time due to the World Superbike (WSBK) event being held in Mandalika, the rising poverty rate in Mataram has continued to fluctuate. For example, in 2021, the city's poverty rate increased. Economic growth, inflation, and the construction of transportation infrastructure all partially and concurrently contribute to Mataram City's poverty rate. Descriptive and associative quantitative methods are used in this study. Using multiple linear regression analysis methodologies, secondary and time series data from According to the study's findings, just one factor—inflation—had a substantial impact on the poverty rate in Mataram, whereas the open unemployment rate, road length, and economic growth had no discernible effects. The poverty rate in the city of Mataram is significantly impacted by the open unemployment rate, road length, inflation, and economic growth all at the same time. The development of MSMEs based on the creative economy, the creation of an appropriate city road network that will be more beneficial to the community's economy, targeted fiscal policies to lower the rate of inflation, and other suggestions are some ways the Mataram city government can try to alleviate poverty, and designing the right strategy to optimize foreign trade.